Remote Work Preferences and Experiences with Distance Learning - Empirical Research - Aleksandra BORKOWSKA; Małgorzata KOSAŁA; Małgorzata ZAKRZEWSKA (Communications of International Proceedings, 2022)
Working remotely is a very important topic, especially after the Covid-19 pandemic, where most industries have had the opportunity to experience it. The main purpose of this paper is to present the advantages and disadvantages of remote work. It also presents the results of empirical studies examining the willingness to work remotely in the future of high school students in relation to their experience of distance learning. The paper answers four research questions: what is the attitude of young people to working remotely, is there any difference among the willingness to work remotely among men and women, what is the impact of personal preferences related to the Internet such as learning online on willingness to work remotely, is there any correlation between willingness to work remotely and willingness to have online classes in the future when the pandemic is over?
Keywords: Distance learning; Remote work; Secondary school students